A phase I clinical trial of ruxolitinib in combination with nilotinib in chronic myeloid leukemia patients with molecular evidence of disease - Sweet, Kendra (Leuk Res, 2018)
PURPOSE: Preclinical evidence indicates that the bone marrow microenvironment provides a protective niche for leukemic stem cells, allowing them to evade the effects of BCR-ABL tyrosine kinase inhibitors (TKIs), but that targeting of the JAK-STAT pathway with the JAK2 inhibitor ruxolitinib increases TKI-induced apoptosis. A phase I clinical trial (NCT01702064) investigated the tolerability and safety of treating chronic-phase chronic myeloid leukemia patients with ruxolitinib in combination with the BCR-ABL TKI nilotinib and explored initial efficacy evidence. EXPERIMENTAL DESIGN: Eleven patients already treated with single-agent nilotinib (300–400 mg twice daily) commenced combination therapy, and molecular responses were evaluated after 6 months. Three ruxolitinib dose cohorts were studied: 5 mg, 10 mg, and 15 mg twice daily. RESULTS: One patient experienced a grade 3/4 adverse event (hypophosphatemia) and 36% of patients experienced grade 1/2 anemia. Of 10 patients who were evaluable for responses, 40% had undetectable BCR-ABL transcripts, as measured by quantitative RT-PCR after 6 months. Plasma inhibitory assay results revealed a decrease in phospho-STAT3 levels after treatment with ruxolitinib. The recommended phase 2 dose of ruxolitinib was 15 mg BID. CONCLUSIONS: Overall, this combination was safe and well-tolerated, and the molecular responses were encouraging, thereby warranting further investigation in a phase 2 trial.